MODERN METHODS OF VALUATION OF ENTERPRISES AND ITS FUTURE CHALLENGES - Miciuła, Ireneusz Maciej (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
In today’s world the valuation of the company as a measure of the efficiency of its operations is of great importance for the functioning of the future. Knowledge about how much the company is worth is of fundamental importance at the time of a commercial transaction, as well as the possibility of its business. Presents the objectives of the valuation of the company and company specific life stages at which such a valuation is required. In the paper the classification of valuation methods used in modern enterprises. On this basis, the methodology of the valuation by the concept of MDI–R (Assets, Income, Intellectual Capital – Market), which measures the effectiveness of a broad spectrum of activities of the company and in accordance with the current characteristics of a good valuation seeks to determine the fair value of the company. At the same time an attempt to draw attention to the risks arising from modern methods of business valuation and its challenges in the future.